2017
DOI: 10.1002/zaac.201700082
|View full text |Cite
|
Sign up to set email alerts
|

Rare Earth Chalcogels NaLnSnS4 (Ln = Y, Gd, Tb) for Selective Adsorption of Volatile Hydrocarbons and Gases

Abstract: The synthesis and characterization of the rare earth chalcogenide aerogels NaYSnS4, NaGdSnS4, and NaTbSnS4 is reported. Rare earth metal ions like Y3+, Gd3+, and Tb3+ react with the chalcogenide clusters [SnS4]4– in aqueous formamide solution forming extended polymeric networks by gelation. Aerogels obtained after supercritical drying have BET surface areas of 649 m2·g–1 (NaYSnS4), 479 m2·g–1 (NaGdSnS4), and 354 m2·g–1 (NaTbSnS4). Electron microscopy and physisorption studies reveal that the new materials have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
2
3
0
Order By: Relevance
“…It can be seen that the parent aerogel showed a CO 2 capacity of 1.4 mmol · g –1 , which is very close to the value reported in a previous study under the same temperature ,. [22b], [22c] By doping the aerogel with a small amount of Pd, the CO 2 uptake had been apparently enhanced at all pressures up to 1.89 mmol · g –1 for 3 wt % Pd @ KY(P 2 S 6 ) 2 , 1.5 mmol · g –1 for 5 wt % Pd @ KY(P 2 S 6 ) 2 , and 1.63 mmol · g –1 for 1 wt % Pd @ KY(P 2 S 6 ) 2 (Figure ).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…It can be seen that the parent aerogel showed a CO 2 capacity of 1.4 mmol · g –1 , which is very close to the value reported in a previous study under the same temperature ,. [22b], [22c] By doping the aerogel with a small amount of Pd, the CO 2 uptake had been apparently enhanced at all pressures up to 1.89 mmol · g –1 for 3 wt % Pd @ KY(P 2 S 6 ) 2 , 1.5 mmol · g –1 for 5 wt % Pd @ KY(P 2 S 6 ) 2 , and 1.63 mmol · g –1 for 1 wt % Pd @ KY(P 2 S 6 ) 2 (Figure ).…”
Section: Resultssupporting
confidence: 87%
“…It can be seen that all the isotherms exhibited a sharp increase in adsorption amount. The saturated adsorption capacity of toluene on the parent aerogel in this study was estimated to be 703 mg · g –1 (8 mmol · g –1 ), which is close to the reported values of toluene adsorption on metal chalcogenide aerogels ,. [22b], [22c] Comparing with the parent aerogel, the PdCl 2 ‐functionalized aerogel exhibited increased saturated adsorption capacity for toluene at room temperature (Table ).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Starting with the works of James A. Ibers [1], compounds of general composition A II Ln III BX 3 , where A is an alkaline earth metal or europium, Ln is an element of the 4f subgroup, B is copper or silver, and X is a chalcogen, increasingly attract researcher's attention [2][3][4][5]. The presence of 3d, 4f elements in the composition of quaternary compounds makes them promising materials in the field of catalysis [6,7], nonlinear optics [8][9][10][11][12][13][14], and thermoelectricity [15]. EuLnCuS 3 exhibit ferro-and ferrimagnetic transitions at temperatures 4.5-5.4 K [16].…”
Section: Introductionmentioning
confidence: 99%